Daily patterns of fatigue after subarachnoid haemorrhage: an ecological momentary assessment study - Elisabeth A. de Vries; Majanka H. Heijenbrok-Kal; Fop van Kooten; Marco Giurgiu; Ulrich W. Ebner-Priemer; Gerard M. Ribbers; Rita J.G. van den Berg-Emons; Johannes B. J. Bussmann (Medical Journals Sweden, 2023)
Objective: To examine the daily course of, and factors associated with, momentary fatigue after subarachnoid haemorrhage, and to explore subgroups of patients with distinct diurnal patterns of fatigue. Design: Observational study using ecological momentary assessment. Subjects: A total of 41 participants with subarachnoid haemorrhage. Methods: Patients with fatigue were included within one year post-onset. Momentary fatigue (scale 1-7) was assessed with repeated measurements (10-11 times/day) during 7 consecutive days. Multilevel-mixed-model analyses and latent-class trajectory modelling were conducted. Results: Mean (standard deviation; SD) age of the group was 53.9 (13.0) years, 56% female, and mean (SD) time post-subarachnoid haemorrhage onset was 9.3 (3.2) months. Mean (SD) momentary fatigue over all days was 3.22 (1.47). Fatigue increased significantly (p < 0.001) over the day, and experiencing more burden of fatigue and day type (working day vs weekend day) were significantly (p < 0.05) associated with higher momentary fatigue. Three subgroups could be distinguished based on diurnal patterns of fatigue. The largest group (n = 17, 41.5%) showed an increasing daily pattern of fatigue. Conclusion: Momentary fatigue in patients with subarachnoid haemorrhage increases over the day, and diurnal patterns of fatigue differ between  participants. In addition to conventional measures, momentary measures of fatigue might provide valuable information for physicians to optimize personalized management of fatigue after subarachnoid haemorrhage.